a) P=(-1)^1*(-1)^2*...*(-1)^2007=(-1)^(1+2+3+...+2007)=(-1)^(2007*2008/2)=(-1)^(2007*1004). Cum 2007*1004 este numar par => P=1.
b) S=(-1)^1+(-1)^2+...+(-1)^2007=[(-1)^1+(-1)^2]+[(-1)^3+(-1)^4]+...+[(-1)^2005+(-1)^2006]+(-1)^2007=[-1+1]+[-1+1]+...+[-1+1]-1=-1.
c) (-1)^1-(-1)^2-...-(-1)^2007=2*(-1)^1-[(-1)^1+(-1)^2+...+(-1)^2007]=-2-S=-2+1=-1.
d) O formula: 1+3+5+...+(2n-1)=n^2, oricare ar fi n natural nenul.
Deci 1*(-1)^1+2*(-1)^2+...+2007*(-1)^2007=-(1+3+5+...+2007)+(2+4+6+...+2006)=-1004^2+2*(1+2+3+...+1003)=-1004^2+2*1003*1004/2= -1004^2+1003*1004=1004*(-1004+1003)=-1004.